Interaction among Cells of Bone, Immune System, and Solid Tumors Leads to Bone Metastases - Ilaria Roato (Clinical and Developmental Immunology)
Bone metastases are a dismal consequence for different types of solid tumors, such as breast, prostate, lung, and kidney cancer. The mechanisms regulating the interactions among bone, immune system, and tumor cells have been deeply investigated, and many studies are ongoing to define the specific role of the different cells in the bone metastatic process. The affinity of some tumors to growth in bone results from the special microenvironment provided by bone. Moreover, immune system and bone have a bidirectional relationship: bone cells express surface molecules ruling the expansion of hemopoietic stem cells from which all cells of the mammalian immune system derive, and various immunoregulatory cytokines influence the fate of bone cells. The last findings allow to extend the concept of vicious cycle and add T cells as mediators of the tumor growth in bone.